Instructive feedback to expand listener skills in a second language in children with autism spectrum disorder. (15th November 2021) - Jimenez‐Gomez, Corina; Pichardo, Jessebelle; Ryan, Victoria
Abstract: Children with autism spectrum disorder (ASD) who live in homes in which the primary language is different than the predominant language in their community need to be able to engage in listener skills in both languages in order to be successful across environments (e.g., school vs. home). Instructional strategies that promote effective acquisition of maximum skills with minimal training are optimal for bilingual children with ASD. The present study evaluated whether teaching listener skills in English while providing instructive feedback in Spanish to three boys with ASD would result in participants displaying the listener skill when presented with the Spanish discriminative stimulus. Participants displayed various levels of transfer from English to Spanish listener responses, with a total of 12 out of the 18 possible transfer targets displayed without direct instruction.